Design and simulation of a thermoelectric cooling system for motorcyclist helmet - Hrairi, Meftah; Abdullah, Abdullah F.; Ahmed, Mirghani Ishak (2012)
The objective of this paper is to design and build an air conditioned motorcyclist helmet. The design of the battery-powered helmet is based on the principles of a thermoelectric module (Peltier effect) to create a hot side and a cold side. The cold side of the thermoelectric module is utilized to provide cooling to the inside helmet space. On the other hand, the heat from the hot side of the module is rejected to ambient surroundings by using heat sinks and fans. The designed thermoelectric cooled helmet was simulated using the finite element software ANSYS as well as experimentally tested for the cooling purpose. The numerical and experimental results showed a good agreement and indicated that the temperature inside the helmet was reduced from 25.5 °C to 19.3 °C in approximately 6 min.